An Investigation into Factors Affecting University Employee Commercial Banks’ Borrowing: Case of Egerton University - Kalui, Fredrick Mukoma; Mulwa, David Musyoki; Oira, Peter O. (Journal for Humanity Science and English Language, 2014)
The study was meant to examine the factors affecting borrowing amongst the employees of public universities in Kenya. The locality of the study was Egerton University. The objectives of the study were to identify the factors that influence bank borrowing and determine the relationship between these factors and borrowing among the employees of Egerton University. The population of the study was 1889 employees of Egerton University. A sample of 318 employees was selected through systematic stratified random sampling. Questionnaire was the main tool of data collection. The results of the study were presented through descriptive statistics such as tables, pie charts, bar graphs, and histograms. Regression analysis was used to determine the extent of relationship between dependent and independent variables in the study. From the study, it was established that long repayment period is the most important factor that influences the borrowing levels from commercial banks followed by lack of guarantee. Interest rates were reported to have a moderate influence while gross salary incomes lowly influence the employee borrowing from commercial banks. The study observed that there exist a relationship between the current level of borrowing and the factors that influence employee borrowing. The level of education influences the borrowing levels from commercial bank. High interest rates significantly reduce the borrowing from commercial banks while high gross salary income and need for business start-up finance increases the borrowing from commercial banks
Keywords: Factors affecting borrowing; Commercial Bank